Implementation of Sharia Principles in the Promotion and Distribution of Mie Jahat Patemon Bangkalan MSME Products - Khoirotun Nisa (Al-Iffah: Journal of Islamic Sciences Research, 2025)
This study aims to analyze the application of sharia principles in promotion and distribution at the "Miejahat" UMKM located in Patemon, Bangkalan. In an Islamic perspective, business activities do not only pursue profit, but must also pay attention to ethical values, justice, and blessings. This study uses a qualitative approach through literature review and field studies with interviews, observations, and documentation. The results of the study indicate that "Miejahat" has implemented the principles of honesty in promotion, openness of information, and maintaining product quality in distribution. However, understanding of the concept of sharia marketing is still not formally structured. This study recommends the need for education and assistance to UMKM actors related to sharia marketing to improve professionalism while maintaininSharia Marketing, Promotion, Distribution, UMKM, actors rasionalism while maintaining business blessings